Host Polymorphisms May Impact SARS-CoV-2 Infectivity. Issue 11 (November 2020) - Brest, Patrick; Refae, Sadal; Mograbi, Baharia; Hofman, Paul; Milano, Gerard
Abstract : Based on a broad public database compilation, we support the hypothesis that germinal polymorphisms may regulate the expression of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) cellular target itself and proteases controlling the process of its shedding or, conversely, its internalization. Consequently, a genetic influence on individual susceptibility to coronavirus disease 2019 (COVID-19) infection is strongly suspected.